2018
DOI: 10.1590/1806-9061-2017-0679
|View full text |Cite
|
Sign up to set email alerts
|

Some Physical, Morphological, and Mechanical Characteristics of Turkey (Meleagris gallopavo) Eggs

Abstract: , respectively. Eggs collected during second laying cycle were, on average, larger and heavier in comparison with those collected during first cycle. Average albumen, yolk and eggshell percentages of the eggs collected during two laying cycles were 58.11%, 29.50% and 12.39%, respectively. The highest breaking strength was obtained when the eggs were loaded along the X-front axis and the least breaking strength was required along the Z-axis. The average breaking strength, absorbed energy and firmness in loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
2
0
1
Order By: Relevance
“…The weight, albumin weight, yolk weight, shell weight, albumin proportion, yolk proportion and shell proportion of the eggs coming from the turkey found in this study were variable. Compared with the results obtain by Galic et al (2018), the weight and weight of the yolk were similar to all data reported in this study. In terms of volume, the albumin weight, shell weight and albumin percentage demonstrated higher values within both mentioned research cycles; while the yolk percentage was less in the study and only the shell percentages were similar within both cycles.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The weight, albumin weight, yolk weight, shell weight, albumin proportion, yolk proportion and shell proportion of the eggs coming from the turkey found in this study were variable. Compared with the results obtain by Galic et al (2018), the weight and weight of the yolk were similar to all data reported in this study. In terms of volume, the albumin weight, shell weight and albumin percentage demonstrated higher values within both mentioned research cycles; while the yolk percentage was less in the study and only the shell percentages were similar within both cycles.…”
Section: Resultssupporting
confidence: 90%
“…In terms of volume, the albumin weight, shell weight and albumin percentage demonstrated higher values within both mentioned research cycles; while the yolk percentage was less in the study and only the shell percentages were similar within both cycles. These variations may have been due to the conditions and exposure type in which the turkeys were raised (Galic et al, 2018). According to González et al (2018), the reported date for protein and fat in the quail eggs were 13.11 g/100 g. These data were slightly higher in protein and fat according to this study, while the data by Congjiao Sun et al (2019) had lower protein and ash levels from the chicken, quail, turkey and duck eggs.…”
Section: Resultsmentioning
confidence: 99%
“…EW, PD and ED values were 75.54 ± 8.07 g, 5.25 ± 0.80 cm and 3.45 ± 0.81 cm, respectively. These data are different from those reported in local turkeys raised in regions of Nigerian (Adeyeye, 2009;Isidahomen et al, 2014;Popoola et al, 2015), Croatia (Galic et al, 2017), Bulgaria (Hristakieva et al., 2017) and India (Anna-Anandh et al, 2012). Previously, it has been described that, in this poultry species, the main factors that influence the variation of external egg traits, mainly in weight, are the genotype (Isidahomen et al, 2014), the phenotype (Juárez-Caratachea et al,2018) and the age of the birds (Ghane et al, 2015;Mróz et al, 2019).…”
Section: Evaluation Of External and Internal Egg Quality Traitsmentioning
confidence: 56%
“…Telur burung Gosong Filipina (Megapodius cumingii) Data karakteristik warna, bentuk dan tekstur telur burung filipina didukung oleh data pada spesies megapoda yang lain yaitu pada burung maleo dan burung mamoa. Sifat fisik, morfologi, dan mekanik telur memegang peranan penting dalam proses perkembangan embrio dan penetasan telur [18]. Selanjutnya dilaporkan juga bahwa parameter morfometrik telur seperti bobot telur, lebar telur, bobot albumen dan kuning telur sangat penting pada unggas karena faktor tersebut mempengaruhi kualitas dan penilaian telur serta perkembangan embrio [19].…”
Section: Hasil Dan Diskusi Karakteristik Fisik Telur Burung Gosong Fi...unclassified